Pengaruh Konsentrasi Ion Aktif Erbium (Er3+) pada Sifat Fisis Medium Gelas Borat-Lithium: Juniastel Rajagukguk, Fitrilawati - Juniastel Rajagukguk Juniastel Rajagukguk; Fitrilawati Fitrilawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2018)
Lithium-borate glasses medium doped Erbium (Er3+) active ion have been prepared by melting-quenching technique. The glasses medium followed composition (mol%): (65-x)B2O3 - 5ZnO - 5Li2O - 15 Na2O - 10PbO - xEr2O3 (with x = 0; 0,05; 0,1; 0,5; 1,0; 2,0 dan 4,0 mol%). Sample with powder form are mixed in the crucible alumina and melted at temperature 12000 C by using of electrical furnance. After poured in to stainless stell, glasses sample were annealed with the decreases rate 70 C per minute. Physical properties og glass medium such as density, molar volume and refractive index were inviestigated. From measured results can be known that Er3+ ion doped with lithium borate glass can affect physical properties of glass host medium. Density of glass is increased from 2.96 gr/cm3 (x = 0.1 mol%) to 3.185 gr/cm3 (x = 4 mol%). Refractive index of glass medium also increased with addition Er3+ ion concentration. The maximum refractive index is obtained when Er 3+ ion concentration of 2.0 mol%. Based on research results can be explained that Er3+ doped Lithium-Borat glasses can be used as one of optical gain candidate.